Fabrication and characteristization of silicon based vertical electrode nanogap biosensor for protein detection - Norbi Hayati Mohd Noor (Universiti Malaysia Perlis, 2010)
This paper provides a case study of nanogap biosensor which has attracted attention among the reserachers due to the potential application in nanotechnology. This nanogap device which are fabricated using standards Complimentary Metal Oxide Semiconductor (CMOS) technology, have the potential to serve as the biomolecular junction because their sizes reduces electrode polarization effect regardless of frequency. This junction technology is essentially a biology-to-digital coverter system that enables real time conversion of biomolecular dielectric signals into digital information.The study is carried out using a heavily doped silicon substrate electrode and poly-silicon electrode vertically separated by afixed distabce of 80 nm silicon oxide spacer. The process flow development in this resesarch consist of details parameters and recipes to define the nanogap spacer. Two (2) types of mask are used in the process which are the Electrode Mask and Aluminium Pad mask. The main focus of this resesarch is to create the gap spacer by using Inductive Coupled Plasma-Reactive Ion Etch (ICP-RIE) to etch the ;oly-silicon layer and buffered hydrofluoric acid (HF) to etch the silicon oxide layer. The overall goal of this research is to design, fabricate, characterize, and test the silicon based vertical electrode nanogap biosensor that will be used to detect and identify target proteins in aqueous solution.